2017
DOI: 10.1186/s41239-017-0061-2
|View full text |Cite|
|
Sign up to set email alerts
|

“From Making to Learning”: introducing Dev Camps as an educational paradigm for Re-inventing Problem-based Learning

Abstract: Dev Camps are events that enable participants to tackle challenges using software tools and different kinds of hardware devices in collaborative project-style activities. The participants conceptualize and develop their solutions in a self-directed way, involving technical, organizational and social skills. In this sense, they are autonomous producers or "makers". The Dev Camp activity format resonates with skills such as communication, critical thinking, creativity, decision-making and planning and can be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
9
0
5
Order By: Relevance
“…[22] categorized the benefits of collaborative learning into four dimensions: social, psychological, academic, and assessmentbased. With the consideration of those benefits, teaching professionals are holding collaborative social learning events such as 'hackathons', 'hack days', or 'coding' or 'dev camps' to foster twenty-first-century learning skills, which aim to create usable products or software by fostering team-based creativity and innovation [8].…”
Section: Learning Through Intensive and Collaborative Probem-solving mentioning
confidence: 99%
See 1 more Smart Citation
“…[22] categorized the benefits of collaborative learning into four dimensions: social, psychological, academic, and assessmentbased. With the consideration of those benefits, teaching professionals are holding collaborative social learning events such as 'hackathons', 'hack days', or 'coding' or 'dev camps' to foster twenty-first-century learning skills, which aim to create usable products or software by fostering team-based creativity and innovation [8].…”
Section: Learning Through Intensive and Collaborative Probem-solving mentioning
confidence: 99%
“…Similarly, nonprofit organizations felt that it was beneficial to get connected with students to support their learning and also to create and visualize something that has only existed as a concept [10]. Also, dev camps can be used for project-project based learning scenarios, as shown in as study where dev camps where co-organized by a company and an university [8]. The facilitator accessed the outcome of the projects on a five-point Likert scale and found that all the results Hackathons in software engineering education -lessons learned from a decade of events went beyond expectations and fulfilled six dimensions of quality: creativity, novelty, motivation, plausibility, technical soundness, and understandability.…”
Section: Learning Through Intensive and Collaborative Probem-solving mentioning
confidence: 99%
“…Salah satu yang dapat dilakukan yaitu dengan mengembangkan model pembelajaran Project Based Learning sesuai pembelajaran abad 21 bermuatan Tri Kaya Parisudha. Pembelajaran Berbasis Proyek sebagai pembelajaran yang menggunakan Proyek sebagai media dalam proses pembelajaran untuk mencapai kompetensi sikap, pengetahuan dan keterampilan (Chounta et al, 2017;Dumitrescu et al, 2014;Marzuki & Basariah, 2017). Penekanan pembelajaran terletak pada aktivitas-aktivitas peserta didik untuk menghasilkan produk dengan menerapkan keterampilan meneliti, menganalisis, membuat, sampai dengan mempresentasikan produk pembelajaran berdasarkan pengalaman nyata (Irman & Waskito, 2020;Pan et al, 2021;Wijayanti et al, 2016).…”
Section: Pendahuluanunclassified
“…Por último, en los procesos propios, ningún docente contempló algún principio sobre Ingeniería de Software, modelo o metodología de desarrollo. En su lugar, emplearon un proceso de diseño y desarrollo guiado por la retroalimentación de los usuarios finales del sistema (estudiantes y docentes) (Bedregal-Alpaca et al, 2019;Gašević et al, 2017) o por la efectividad que la plataforma tuvo en la mejora del proceso de enseñanza-aprendizaje (Chounta et al, 2017;Flores-Fuentes & Juárez-Ruiz, 2017). Por otra parte, en algunos casos se optó por identificar los componentes de la plataforma que deberían mejorarse, desarrollarse o incluirse.…”
Section: Proceso De Diseño Y Desarrollo De Las Plataformas De Tecnología Educativaunclassified